Pengaruh Shyness Terhadap Kecemasan Komunikasi Interpersonal Pada Mahasiswa Tahun Pertama Fakultas Psikologi Yang Berasal dari Luar Kota Makassar - Ramadhani, Anita; W, Widyastuti; Ridfah, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to determine the effect of shyness on interpersonal communication anxiety in first-year students of the Faculty of Psychology who come from outside Makassar City. Respondents in this study were 106 first-year students of the Faculty of Psychology who migrated or came from outside the agglomeration area. The results of data analysis using exponential regression analysis show a significant value of 0.000, meaning that shyness affects interpersonal communication anxiety in first-year students who come from outside Makassar City. The R-value is 0.760, indicating that shyness and interpersonal communication anxiety are in a very strong category. The R Square value is 0.577, meaning that shyness affects interpersonal communication anxiety, contributing 57.7%..